A sulfur self‐doped multifunctional biochar catalyst for overall water splitting and a supercapacitor from Camellia japonica flowers. Issue 4 (30th April 2022) - Xia, Chengkai; Surendran, Subramani; Ji, Seulgi; Kim, Dohun; Chae, Yujin; Kim, Jaekyum; Je, Minyeong; Han, Mi‐Kyung; Choe, Woo‐Seok; Choi, Chang Hyuck; Choi, Heechae; Kim, Jung Kyu; et al.
Abstract: A versatile use of a sulfur self‐doped biochar derived from Camellia japonica (camellia) flowers is demonstrated as a multifunctional catalyst for overall water splitting and a supercapacitor. The native sulfur content in the camellia flower facilitates in situ self‐doping of sulfur, which highly activates the camellia‐driven biochar (SA‐Came) as a multifunctional catalyst with the enhanced electron‐transfer ability and long‐term durability. For water splitting, an SA‐Came‐based electrode is highly stable and shows reaction activities in both hydrogen and oxygen evolution reactions, with overpotentials of 154 and 362 mV at 10 mA cm −2, respectively. For supercapacitors, SA‐Came achieves a specific capacitance of 125.42 F g −1 at 2 A g −1 and high cyclic stability in a three‐electrode system in a 1 M KOH electrolyte. It demonstrated a high energy density of 34.54 Wh kg −1 at a power density of 1600 W kg −1 as a symmetric hybrid supercapacitor device with a wide working potential range of 0–1.6 V. Abstract : Sulfur self‐doped biochar (SA‐Came) derived from Camellia japonica flowers was formulated as a multifunctional electrode for overall water splitting and supercapacitor application. The SA‐Came electrodes are fabricated for full water splitting and a symmetric hybrid supercapacitor. This study demonstrates the ingenious potential of a single sulfur self‐doped biochar material that possesses multifunctional capabilities to formulate high energy storage and conversion systems.